"Are we getting the biometric bioethics right?" – the use of biometrics within the healthcare system in Malawi. Issue 1 (1st January 2020) - Mwapasa, Mphatso; Gooding, Kate; Kumwenda, Moses; Nliwasa, Marriott; Kaswaswa, Kruger; Sambakunsi, Rodrick; Parker, Michael; Bull, Susan; Desmond, Nicola
ABSTRACT: Biometrics is the science of establishing the identity of an individual based on their physical attributes. Ethical concerns surrounding the appropriate use of biometrics have been raised, especially in resource-poor settings. A qualitative investigation was conducted to explore biometrics clients ( n = 14), implementers ( n = 12) and policy makers as well as bioethicists ( n = 4) perceptions of the ethical aspects of implementing biometrics within the healthcare system in Malawi. Informed use, privacy and confidentiality as well as perceptions of benefits and harms were identified as major issues in the application of biometrics. Implementation of biometrics within the healthcare system in Malawi poses a range of potential ethical issues and practical challenges that impact on equitable uptake. There is a need for more research to explore the benefits and harms of biometrics in practice. Improved community engagement and sensitization should be a required component of biometrics introduction in Malawi.